2017
DOI: 10.18203/2319-2003.ijbcp20164509
|View full text |Cite
|
Sign up to set email alerts
|

A study to determine the knowledge and level of awareness of medical undergraduates about herbal medicines and herb-drug interactions

Abstract: Background:The increasing usage of herbal medicines worldwide has increased the probability of co-administration of herbal and allopathic medicines. This may lead to serious safety concerns, including herb-drug interactions (HDIs). Many HDIs may be overlooked due to poor doctor-patient communication about herbal drug usage probably because of lack of knowledge of herbal medicines and HDIs among physicians. The study was thus planned to identify the knowledge and awareness of medical students regarding the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The results of the survey showed that 12% of participants have more trust in pharmacists' advice than in physicians' advice. Studies of Nur (2010), Howell et al (2006) and Boparai et al (2017) have shown that there is no proper communication between physicians and patients and that patients do not inform the physician about the use of herbal preparations. The results of the studies of Samojlik et al (2013) and Newberry et al (2001) have shown that 88.9% and 75% of participants, respectively, answered that they do not consider that it is important to emphasize that they use the herbal preparation with the prescribed therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the survey showed that 12% of participants have more trust in pharmacists' advice than in physicians' advice. Studies of Nur (2010), Howell et al (2006) and Boparai et al (2017) have shown that there is no proper communication between physicians and patients and that patients do not inform the physician about the use of herbal preparations. The results of the studies of Samojlik et al (2013) and Newberry et al (2001) have shown that 88.9% and 75% of participants, respectively, answered that they do not consider that it is important to emphasize that they use the herbal preparation with the prescribed therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, another systematic evaluation of 26 studies of herbal and complementary medicine practice among nursing students found a positive opinion of herbal and complementary medicine therapies, despite their inadequate knowledge [25]. Similarly, studies from developed countries reported that most of the students knew that herbs could interact with conventional drugs when administered concurrently, but students failed to provide specific examples of such interactions [26,27]. In Saudi Arabia, the HDI initiative was started by the Saudi Food and Drug Authority to identify and evaluate possible HDIs and guarantee patients' safety [28].…”
Section: Introductionmentioning
confidence: 99%
“…The nurse's role in various aspects of health care is well documented, including patient counseling and education [31]. Nurses play an important role in the safe and effective use of medications, and they are frequently involved in delivering medications to their patients [26,27,31]. From the viewpoint that nursing undergraduates are future practicing HCPs, possessing adequate knowledge about HDIs in their undergraduate education not only helps in achieving excellent grades but also helps in their future practice.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although some medical schools offer adequate medical education for CAM, the proportion of medical schools in the world offering such a training is very low. 9 Studies have shown that medical students have limited knowledge about CAM and medicinal plants. 18,19 There are also very few medical schools in Turkey providing education about herbal products.…”
mentioning
confidence: 99%
“…20 In general, most of the studies were about the knowledge and the perception of medical students about CAM. 9,[18][19][20][21] In this study, it was aimed to determine the types of medicinal herbs and herbal products, reasons of use and consciousness levels in the first three years students of the Dokuz Eylul University, School of Medicine. Our study is also the first ever survey in Turkey, assessing whether medical students have any information about the legal regulations issued on medicinal herbs and herbal products.…”
mentioning
confidence: 99%